DINAMIKA STRUKTUR PASAR DAN TANTANGAN DAYA SAING USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI INDONESIA - Suvianti, Evi; Aprilia, Tasya Dwi; Cahyati, Nadila Arsita; Saputri, Eti; Yunita, Y (Jurnal Ekonomi & Bisnis, 2025)
MSMEs hold a pivotal position within Indonesia's economic landscape. MSMEs serve as the primary driving force of the informal sector, which plays a critical part in maintaining national economic stability. Although MSMEs contribute significantly to national economic growth and poverty reduction, the sector continues to face various structural and technical challenges that hinder its sustainable competitiveness. This study seeks to explore the evolving structure of the MSME market and to identify key factors influencing its competitiveness, both from the internal aspects of the enterprises and from external systemic factors. This study used a qualitative method with a literature review approach. In the context of this research, the literature study method is used as a descriptive basis for compiling an analytical narrative regarding the structure of the MSME market and the challenges faced in the context of competitiveness, by utilizing available secondary data in a comprehensive and systematic manner. The results of this study indicate that the market structure of MSMEs in Indonesia was characterized by high dynamism, reflected in intense competition, product diversity, and a predominance of local markets that have not been systematically integrated into national supply chains or the global economy. Some of the major challenges confronting MSMEs include capital constraints, weak managerial capacity, insufficient application of technology, lack of product innovation and less adaptive market expansion strategies. Therefore, this study was expected to generate strategic policy recommendations aimed at strengthening the role of MSMEs as the backbone of an inclusive, adaptive, and sustainable national economy.